Analisis Kompetensi Guru Dan Lingkungan Madrasah Terhadap Motivasi Belajar Siswa MTsN 1 Kota Blitar - Premintari, Diana Aries; Tantowi, Ahmad (Universitas Islam Kadiri, 2025)
The success of the goal of education in madrasah depends on the educational resources owned. Madrasah which is a religious-based educational institution has complex and abundant resources. This study aims: (1) To analyze teacher competence partially influencing the learning motivation of students of MTsN 1 Kota Blitar. (2) To analyze the madrasah environment partially influencing the learning motivation of students of MTsN 1 Kota Blitar. (3) To analyze teacher competence and madrasah environment simultaneously influencing the learning motivation of students of MTsN 1 Kota Blitar. (4) To analyze the variables of teacher competence and madrasah environment that have a dominant influence on the learning motivation of students of MTsN 1 Kota Blitar. This study uses a quantitative analysis method, namely analysis of data that has been scored according to the measurement scale that has been determined using statistical formulas. The analysis used is data in the form of numbers. While the quality test uses (1) Descriptive statistical analysis, (2) Verification analysis. (3) Classical assumption test (4) Multiple regression analysis, and (5) Hypothesis testing, (6) Determination Coefficient Analysis (R2). The results of the study indicate that: (1) Teacher Competence partially has a significant influence on Student Learning Motivation at MTsN 1 Kota Blitar. (2) Madrasah Environment partially has a significant influence on Student Learning Motivation at MTsN 1 Kota Blitar. (3) Teacher Competence and Madrasah Environment simultaneously have a significant influence on Student Learning Motivation at MTsN 1 Kota Blitar. (4) Teacher Competence has the most dominant influence on Student Learning Motivation at MTsN 1 Kota Blitar.